Research and Simulation of Cornering Characteristics on Oil and Gas Pipeline Robots - Xia Wenfeng; Yu Jiuyang; Dai Yaonan; Cheng Hang; Zhang Dean; Hu Tianhao (Jixie chuandong)
Aiming at the problems that the pipeline robot is difficult to turn and has poor moving stability in the variable diameter pipeline, an adaptive oil and gas pipeline robot is studied; adopting a variable-diameter two-track and one-roller-supported moving mechanism, the stable movement of the robot in the pipeline is ensured. Theoretical research on the passage of oil and gas pipeline robots in the pipeline is conducted, and the size of the robot is determined; the dynamics of the robot's turning performance is studied by Adams. The simulation results show that the robot can successfully complete the turning movement in the 600 mm pipeline, and therefore it is determined that the torque provided by the motor should be greater than 90 N<alternatives>∙ <?fx-imagestate width="1.86266661" height="2.62466669"?> <?fx-imagestate width="1.86266661" height="2.62466669"?> </alternatives>m. Experimental studies have found that the speed value of the experimental measurement is consistent with the simulation results, which verifies the rationality of the design.